Youth as a Representation of Essentialities of Human Being - Drapushko, R. G; Drapushko, N. A (Anthropological Measurements of Philosophical Research, 2022)
Purpose. This article reveals the importance of the analysis of the theory of generations to identify the essential characteristics of the phenomenon of youth. Theoretical basis of this study is socio-philosophical anthropology, i.e. philosophical anthropology using certain methods of sociological, socio-psychological and ethnological research, as well as philosophical comprehension of the application of these methods in special sciences. Originality. The authors rethought the theoretical and practical potential of generational theory through its reconceptualization based on philosophical anthropology, which created an opportunity to shift research attention from the attempts to identify superhistorical characteristics of youth to the identification of the essential nature of specific historical and sociocultural features of young people as representatives of a particular culture. Conclusions. Defining the youth phenomenon requires accounting at least three constraints that on the one hand, play a role of warnings that deter from theoretical and practical errors in the study of the youth phenomenon, and on the other hand, guidelines for identifying real, specific characteristics of youth as a social phenomenon. Limitations of theoretical and practical analysis of young people are as follows: first, the need to consider demographic data not as final, but only as initial and preliminary, such that require further substantive socio-cultural analysis; second, the inadmissibility of ignoring the cultural diversity of the manifestations of the youth phenomenon, instead the need to identify the special characteristics of youth of different ethnic, religious and other groups; third, the need to take into account the specifics of self-identification of those who identify themselves as young people as a social group.